Complications of central venous catheter in patients transplanted with hematopoietic stem cells in a specialized service - Lidiane Miotto Barretta; Lúcia Marinilza Beccaria; Cláudia Bernardi Cesarino; Maria Helena Pinto (Universidade de São Paulo, 2016)
Abstract Objective: to identify the model, average length of stay on site and complications of central venous catheter in patients undergoing transplant of hematopoietic stem cells and verify the corresponding relationship between the variables: age, gender, medical diagnosis, type of transplant, implanted catheter and insertion site. Method: a retrospective and quantitative study with a sample of 188 patients transplanted records between 2007 and 2011. Results: the majority of patients used Hickman catheter with an average length of stay on site of 47.6 days. The complication fever/bacteremia was significant in young males with non-Hodgkin's lymphoma undergoing autologous transplant, which remained with the device for a long period in the subclavian vein. Conclusion: nurses should plan with their team the minimum waiting time, recommended between the catheter insertion and start of the conditioning regimen, as well as not to extend the length of time that catheter should be on site and undertake their continuing education, focusing on the prevention of complications.